(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This paper examines psychologism as a vital element of Alexander Pushkin’s artistic method in the novel Eugene Onegin. Particular attention is paid to the techniques used to depict the characters’ inner worlds, their emotional and moral experiences, and the motives behind their actions. The study analyzes the interaction between the author and the protagonists, the influence of social and cultural contexts on character formation, and the role of narration and internal monologues in conveying the subtle nuances of psychological life.